Prevalence and diversity of gastrointestinal parasites in free‐ranging rhesus macaques (Macaca mulatta) in different land gradients of Bangladesh. Issue 1 (15th November 2021) - Islam, Shariful; Rahman, Md. Kaisar; Uddin, Md. Helal; Rahman, Md. Mustafizur; Chowdhury, Mohammad N. U.; Hassan, Mohammad M.; Magalhaes, Ricardo S.; Islam, Ariful
Abstract: Rhesus macaques are considered an important reservoir of different gastrointestinal (GI) zoonotic parasites affecting livestock and humans. Loads of GI parasites in the free‐ranging rhesus macaques living in close proximity to communities in Bangladesh are still unknown. To estimate the prevalence and diversity of zoonotic GI parasites in rhesus macaques of Bangladesh, a total of 182 freshly voided fecal samples were collected from macaques living in rural ( N  = 67), peri‐urban ( N  = 57), urban ( N  = 28), and Safari park ( N  = 30) between October 2015 and December 2016. All samples were tested by direct smear, sedimentation, flotation, and the McMaster techniques. A total of fourteen different taxa of GI parasites were detected, revealing an overall prevalence of 54.4% ( n  = 99; 95% confidence interval [CI]: 46.9–61.8). The prevalence of GI parasites was found to be significantly correlated with the mean parasitic taxa per individual in a group ( r  = 0.90; p  = 0.002). The multivariable logistic regression analysis showed that the overall prevalence of GI parasites in macaques was significantly higher in those inhabiting rural areas (62.69%; odds ratio [OR]: 7.22; p  = 0.001) and in macaques with interactions with other animals (60.98%; OR: 5.49; p  = 0.005). Our results also indicated that the prevalence of Strongyloides spp. and Balantidium coli infections varied significantly between land gradients. Our results also indicate that macaques frequently visit human settlements for food and are found interacting with domestic animals. In conclusion, the high prevalence of zoonotic GI parasite infection in rhesus macaques found in our study may pose a significant public health risk to communities, particularly in rural areas of Bangladesh. Health promotion to at‐risk communities focusing on limiting contact with rhesus macaques is necessary to mitigate potential zoonotic transmission. Research highlights: Fourteen different taxa of gastrointestinal (GI) parasites were detected, revealing an overall prevalence of infection of 54.4%. Significantly higher prevalence of GI parasites in macaques inhabiting rural areas, where macaques frequently interact with humans and other animals. High prevalence of diverse GI parasite infestation in rhesus macaque s might have a public health concern in Bangladesh. Abstract : Transmission pathways of gastrointestinal parasites infection in rhesus macaques of Bangladesh.